Policy options for fertilizer subsidy reforms in Rwanda: A simulation-based analysis and synthesis of prior studies - Spielman, David J.; Mugabo, Serge; Rosenbach, Gracie; Ndikumana, Sosthene; Benimana, Gilberthe Uwera; Ingabire, Chantal (International Food Policy Research Institute, 2022)
Agricultural input subsidies are a prominent feature in the 2018-2024 Strategic Plan for Agricultural Transformation (PSTA 4), which is designed and implemented by the Ministry of Agriculture and Animal Resources (MINAGRI). By reducing the cost of improved seed and inorganic fertilizers, subsidies are designed to accelerate the use of these productivity-enhancing inputs, thereby increasing agricultural yields and output, increasing rural incomes while reducing food prices, and improving food security in line with PSTA 4’s targets. However, questions arise about whether the current input subsidy rates and levels are sufficient to increase crop production and meet the PSTA 4 targets, and whether the subsidy system can be expanded in the current economic climate and fiscal situation caused by the COVID-19 pandemic and spike in global fertilizer prices. This paper examines the impact of an increase in the price of fertilizer in Rwanda using seasonal production data from National Institute of Statistics of Rwanda (NISR) in a microsimulation model aimed at three priority crops—maize, rice, and Irish potato—and the three main fertilizers in use—diammonium phosphate (DAP), urea, and NPK.